2015
DOI: 10.1095/biolreprod.114.122838
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Beta 8 (ITGB8) Regulates Embryo Implantation Potentially via Controlling the Activity of TGF-B1 in Mice1

Abstract: Integrins (ITGs) are mediators of cell-cell and cell-matrix interactions, which are also associated with embryo implantation processes by controlling the interaction of blastocyst with endometrium. During early pregnancy, ITGbeta8 (ITGB8) has been shown to interact with latent transforming growth factor (TGF) beta 1 (TGFB1) at the fetomaternal interface. However, the precise role of ITGB8 in the uterus and its association with embryo implantation has not been elucidated. Therefore, we attempted to ascertain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 35 publications
5
31
0
Order By: Relevance
“…Importantly, the endometrial luminal epithelial cells sense the implanted blastocyst and accommodate it for pregnancy establishment 27, 28 and ITGB3 has been vital in this process 29, 30 . Further, recently one of our study has demonstrated a prominent expression of ITGB8 in the endometrial epithelial cells 10 . However, apart from the adhesion process of integrin during the lodging process of a blastocyst on the endometrial cells to facilitate the implantation process, they also may trigger the intracellular signaling pathways via various biochemical messengers, but this needs further investigation, which is being reported in the present study.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Importantly, the endometrial luminal epithelial cells sense the implanted blastocyst and accommodate it for pregnancy establishment 27, 28 and ITGB3 has been vital in this process 29, 30 . Further, recently one of our study has demonstrated a prominent expression of ITGB8 in the endometrial epithelial cells 10 . However, apart from the adhesion process of integrin during the lodging process of a blastocyst on the endometrial cells to facilitate the implantation process, they also may trigger the intracellular signaling pathways via various biochemical messengers, but this needs further investigation, which is being reported in the present study.…”
Section: Introductionsupporting
confidence: 52%
“…In our recent report, we have demonstrated the expression of ITGB8 in the endometrium and it was predominant in the luminal epithelial cells, which is essential for embryo implantation process 10 . Importantly, ITGB8 controls the TGF-B activation, which is also one of the crucial signaling in the acqusition of endometrial receptivity for blastocyst implantaiton 10, 31 .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Function-inhibiting antibodies that target integrin αvβ3 or αvβ8 -both of which are expressed on trophectoderm as well as on receptive phase epithelium -RGD peptide and knockdown of epithelial αvβ3 can reduce embryo attachment in vitro (Kaneko et al, 2011(Kaneko et al, , 20132014a) and in vivo (Illera et al, 2000(Illera et al, , 2003Kumar et al, 2015). This implies an interaction between integrin αv and an extracellular bridging ligand (see poster) regarding attachment (Singh and Aplin, 2009).…”
Section: Box 2: Demonstrating Integrin Function In Implantationmentioning
confidence: 99%